The Influence of Job Satisfaction, Responsibility, and Employee Ability on Employee Performance at the Communication and Informatics Service of Batu Bara Regency - Anshari Putra; Neneng Suryani (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study aims to determine the simultaneous and partial effects of job satisfaction, responsibility, and employee competence on the job performance of employees at the Batu Bara Regency Communication and Information Technology Office. Method: This study employed a quantitative descriptive approach. Data analysis was conducted using multiple linear regression analysis, and the sample consisted of 33 respondents selected through the saturation sampling method. Results: The regression equation obtained was Y = 1.526 + 0.161X1 + 0.649X2 + 0.244X3. The results of the F-test showed that job satisfaction, responsibility, and employee competence simultaneously affected work performance, as indicated by the calculated Fvalue (32.737) being greater than the critical Fvalue (2.93). The t-test results revealed that job satisfaction partially affected work performance with a calculated tvalue of 2.650 > 2.042, responsibility affected work performance with a calculated tvalue of 7.623 > 2.042, and employee competence affected work performance with a calculated tvalue of 2.496 > 2.042. Furthermore, the adjusted R² value was 0.748, indicating that job satisfaction, responsibility, and employee competence contributed 74.8% to work performance, while the remaining 25.2% was influenced by other variables outside this study. Conclusion: The study concludes that job satisfaction, responsibility, and employee competence have significant simultaneous and partial effects on employee work performance at the Batu Bara Regency Communication and Information Technology Office.